Epigenetic consequences of interploidal hybridisation in synthetic and natural interspecific potato hybrids - Cara, Nicolás (2019)
Interploidal hybridisation can generate changes in plant chromosome numbers, which might exert effects additional to the expected due to genome merger per se (i.e., genetic, epigenetic and phenotypic novelties).Wild potatoes are suitable to address this question in an evolutionary context. To this end, we performed genetic (AFLP and SSR), epigenetic (MSAP), and cytological comparisons in: i) natural populations of the diploid cytotype of the hybrid taxonomic species Solanum x rechei (2n=2x, 3x) and its parental species, the triploid cytotype of Solanum microdontum (2n=2x, 3x) and Solanum kurtzianum (2n=2x); and ii) newly synthesised intraploidal (2x x 2x) and interploidal (3x x 2x) S. microdontum x S. kurtzianum hybrids.Aneuploidy was detected in S. x rechei and the synthetic interploidal progeny; this phenomenon might have originated the significantly higher number of methylation changes observed in the interploidal vs. the intraploidal hybrids. The wide epigenetic variability induced by interploidal hybridisation is consistent with the novel epigenetic pattern established in S. x rechei compared to its parental species in nature.These results suggest that aneuploid potato lineages can persist throughout the short term, and possibly medium term, and that differences in parental ploidy resulting in aneuploidy are an additional source of epigenetic variation.